Enhancing the language development of toddlers in foster care by promoting foster parents' sensitivity: Results from a randomized controlled trial. Issue 2 (3rd October 2018) - Raby, Kenneth Lee; Freedman, Emily; Yarger, Heather A.; Lind, Teresa; Dozier, Mary
Abstract: Young children in foster care are at increased risk for problematic language development, making early intervention a critical tool in enhancing these children's foundational language abilities. This study examined the efficacy of an early preventative intervention, Attachment and Biobehavioral Catch‐up for Toddlers (ABC‐T), in improving the receptive vocabulary abilities of toddlers placed in foster care. All the children had been removed from their biological parents' care and placed into foster care. When children were between 24 and 36 months old, foster parents were contacted by research staff and consented to participate. Parents were randomly assigned using a random number generator to receive either ABC‐T ( n = 45), which aimed to promote sensitive parenting for children who have experienced early adversity, or a control intervention ( n = 43). Foster children's receptive vocabulary skills were assessed post‐intervention using the Peabody Picture Vocabulary Test, Third Edition, when children were between 36 and 60 months old. Children whose foster parents received ABC‐T demonstrated more advanced receptive vocabulary abilities than children whose foster parents received the control intervention. The positive effect of ABC‐T on foster children's receptive vocabulary was mediated by increases in foster parents' sensitivity during parent–child interactions. Trial registration: ClinicalTrials.gov NCT01261806. Abstract : Young children in foster care are at increased risk for problematic language development. This study demonstrated that Attachment and Biobehavioral Catch‐up for Toddlers, a parenting‐focused intervention, led to improvements in the receptive vocabulary abilities of toddler‐age children in foster care. The positive effect of the intervention on foster children's receptive vocabulary was mediated by increases in foster parents' sensitivity during parent‐child interactions.